CD146 as a Prognostic-Related Biomarker in ccRCC Correlating With Immune Infiltrates - Lv, Zheng; Feng, Hua-Yi; Tao, Wang; Li, Hong-Zhao; Zhang, Xu (Frontiers in Oncology, 2021)
Backgrounds: CD146 was highly expressed in various malignant tumors and associated with the poor prognosis. However, the role of CD146 in clear cell renal cell carcinoma (ccRCC) is still unknown. This study aimed to identify the role of CD146 in ccRCC by integrated bioinformatics analysis. Methods: CD146 mRNA expression and methylation data in ccRCC was examined using the TIMER, UALCAN and MethSurv databases. CD146 expression in paraffin-embedded tissues (140 cancer samples and 140 paracancer tissues) from our cohort were examined by immunohistochemistry assay. The LinkedOmics database was used to study the signaling pathways related to CD146 expression. TIMER and TISIDB were used to analyze the correlations among CD146, CD146-coexpressed genes, tumor-infiltrating immune cells and immunomodulators. The relationship between CD146 and drug response in renal cancer cell lines were analyzed by the CTRP and CCLE database. Results: The mRNA and protein levels of CD146 were elevated in ccRCC tissues than that in paracancer tissues. The DNA methylation of CD146 in ccRCC tissues were lower than that in normal tissues. Importantly, high CD146 expression was associated with poor prognosis in patients with ccRCC. Furthermore, multivariate Cox regression analysis showed that CD146 was an independent prognostic factor in ccRCC. GO and KEGG pathway analysis indicated the co-expressed genes of CD146 were mainly related to a variety of immune-related pathways, including Th1 and Th2 cell differentiation, Th17 cell differentiation, Leukocyte transendothelial migration. Our data demonstrated that the expression and methylation status of CD146 were strongly correlated with immune infiltration levels, immunomodulators, and chemokines. Further, the sensitivity and resistance of renal cancer cell lines to some drugs were related to CD146 expression. Conclusions: Our study highlights the clinical significance of CD146 in ccRCC and provides novel insights into the immune function of CD146 in tumor microenvironment.